Constructing CuNi dual active sites on ZnIn2S4 for highly photocatalytic hydrogen evolution. Issue 8 (24th February 2021) - Jin, Jingyi; Cao, Yanren; Feng, Ting; Li, Yanxin; Wang, Ruonan; Zhao, Kaili; Wang, Wei; Dong, Bohua; Cao, Lixin
Abstract : Novel CuNi bimetal-modified ZnIn2 S4 photocatalysts with enhanced photocatalytic hydrogen evolution performance have been explored. The possible mechanism of the synergistic effect and spillover effect between Cu and Ni were proposed. Abstract : Noble metal Pt as an efficient cocatalyst is widely utilized in the photocatalytic hydrogen (H2 ) evolution field while its application is restricted by high price and scarcity. Herein, a feasible strategy for depositing a non-noble bimetallic cocatalyst on a ZnIn2 S4 surface has been put forward. The low-cost and earth-abundant CuNi bimetal cocatalyst was deposited via a simple one-step photoreduction method. In this novel photocatalytic system, CuNi bimetal served as dual active sites which can inhibit the recombination of charge carriers on ZnIn2 S4 . Compared with single Cu or Ni deposited ZnIn2 S4 samples, CuNi bimetal decorated samples showed a significant enhancement in hydrogen evolution activity. Meanwhile, 12% Cu2 Ni1 –ZIS realized the highest hydrogen generation rate (7825 μmol h −1 g −1, AQE = 30.19%, λ > 420 nm). The enhanced photocatalytic performance can be attributed to the spillover effect of H atoms from Ni to Cu and the synergistic effect between the metals. This work provides a novel strategy for optimizing the H2 evolution performance of a ZnIn2 S4 -based photocatalyst by utilizing a non-noble bimetallic cocatalyst as dual active sites.